Тайна номера 101: повесть / Ф. Келли ; пер. с англ. И. Н. Гилярова - Келли Фиона (Черный котенок, 2003)
6-8кл Экземпляры: ф.1 (2003) / Инвентарный номер: 47312 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: К 34 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44